2011
DOI: 10.2135/cropsci2010.02.0063
|View full text |Cite
|
Sign up to set email alerts
|

Selection for Dry Bean Yield On‐Station Versus On‐Farm Conventional and Organic Production Systems

Abstract: High yielding cultivars adapted to conventional and organic production system would maximize efficiency of nutrient usage and reduce dependence on pesticides. The objective of this study was to determine if separate breeding efforts are needed to obtain high yielding dry bean breeding lines for on‐farm organic (FO) and on‐farm conventional (FC) production systems. The six highest yielding breeding lines selected from each of FO, FC, and on‐station conventional (SC) production systems in two populations (1WS, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Overall, the yield performance of the heirloom genotypes in our study would suggest that incorporation of these genotypes into a modern breeding program for organic production would not introduce significant yield drag. Singh et al (2011) suggested that the use of well-adapted heirloom genotypes in bean breeding could be “crucial for developing high-yielding broadly adapted cultivars for sustainable organic and conventional production systems, thus reducing research and production costs.”…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the yield performance of the heirloom genotypes in our study would suggest that incorporation of these genotypes into a modern breeding program for organic production would not introduce significant yield drag. Singh et al (2011) suggested that the use of well-adapted heirloom genotypes in bean breeding could be “crucial for developing high-yielding broadly adapted cultivars for sustainable organic and conventional production systems, thus reducing research and production costs.”…”
Section: Discussionmentioning
confidence: 99%
“…Such breeding may not produce the traits needed to optimize organic cultivation Murphy et al 2007;Singh et al 2011). Furthermore, plant breeders express concern that seed industry consolidation continues to result in less prominent geographic areas being dropped from the focus of private breeding programs, or "abandonment of the margins" (Tracy 2014:48).…”
Section: Introductionmentioning
confidence: 99%
“…Other genotypes, such as pinto bean Buster and pinto bean Bill Z were responsive to high inputs and may be better suited to systems where fertilizer and supplemental irrigation are used to maximize yield. Singh et al (2011) investigated selection under organic and conventional systems and questioned whether the small gains achieved for production in the respective system were worth the effort. They concluded that direct selection for yield under organic production systems resulted in only slight gains when those genotypes were grown under organic production systems when compared to genotypes which were selected under conventional systems (Singh et al, 2011).…”
mentioning
confidence: 99%
“…Singh et al (2011) investigated selection under organic and conventional systems and questioned whether the small gains achieved for production in the respective system were worth the effort. They concluded that direct selection for yield under organic production systems resulted in only slight gains when those genotypes were grown under organic production systems when compared to genotypes which were selected under conventional systems (Singh et al, 2011). This conclusion suggests that dry beans selected under conventional production systems are well suited to both organic and conventional production systems.…”
mentioning
confidence: 99%